Mating regulates growth, metabolism, and digestive efficiency in the female Drosophila midgut - Tahmineh Kandelouei; Madeline E. Houghton; Mitchell R. Lewis; Caroline C. Keller; Marco Marchetti; Xiaoyu Kang; Bruce A. Edgar (Proceedings of the National Academy of Sciences, 2026)
Adaptive changes in organ size and function occur in most animals, but how these changes are regulated is not well understood. Previous research found that mating in Drosophila females promotes intestinal stem cell proliferation and increases the overall size of the endodermal portion of the intestine (the “midgut”). Other studies reported mating-dependent changes in feeding behavior, midgut gene expression, and whole-body lipid storage, suggesting altered metabolism. Here, we show that mating dramatically alters female midgut metabolism and digestive function. Mating increased relative levels of TCA cycle intermediates, fatty acids, and ceramides in the gut, increased total midgut lipids and protein, and reduced relative carbohydrate levels. Mating also enhanced the efficiency of protein digestion relative to carbohydrate digestion. Corroborating a previous report [M. A. White, A. Bonfini, M. F. Wolfner, N. Buchon, Proc. Natl. Acad. Sci. U.S.A. 118 , e2018112118 (2021)], we found that the expression of genes that mediate protein and carbohydrate and metabolism was similarly altered. In addition, we noted a mating-dependent downregulation of oxidative stress response and autophagy genes. Mating-dependent increases in ecdysone receptor (EcR) signaling were important for increasing TCA cycle intermediates, protein, and ceramides in the female midgut, but had minimal effects on bulk lipid accumulation. Overall, this study contributes to our understanding of the physiological changes that occur during adaptive intestinal growth, and how they are regulated.